2017
DOI: 10.28927/sr.403255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Traverse Velocity and Pump Pressure on the Efficiency of Abrasive Waterjet for Rock Cutting

Abstract: Abstract. This paper presents investigations on the behavior of four types of rocks (syenite, granite, marble and sandstone) subjected to abrasive waterjet cutting. The influence of traverse velocity and pump pressure on the efficiency of cutting is analyzed. Moreover, the influence of the physical-mechanical behavior of the rocks on their removal process is investigated. It was found that, in general, the removed volume of rock and the cutting rate tend to increase with the decrease of traverse velocity and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Karmiris-Obratański et al [ 61 ] investigated the effect of the number of cuts and transverse speed on achieving greater depth of cut in abrasive water jets and found that multiple cuts resulted in better results compared with a single cut, summarizing that the transverse speed was directly proportional to the removal rate of the material being machined but inversely proportional to the depth of cut, surface roughness, and kerf taper. Arab et al [ 62 ] studied the effect of pump pressure and transverse feed rate on the cutting effect of abrasive water jets for cutting four types of rock and found that the removal volume and cutting rate of rocks increased with the increase in pump pressure and decrease in transverse feed rate, and the best cutting efficiency was obtained when the pump pressure was 400 MPa and the transverse feed rate was 200 mm/min. The best cutting efficiency was obtained at a pump pressure of 400 MPa and a transverse feed rate of 200 mm/min.…”
Section: Influencing Factors In the Processing Removal Process Of Abr...mentioning
confidence: 99%
“…Karmiris-Obratański et al [ 61 ] investigated the effect of the number of cuts and transverse speed on achieving greater depth of cut in abrasive water jets and found that multiple cuts resulted in better results compared with a single cut, summarizing that the transverse speed was directly proportional to the removal rate of the material being machined but inversely proportional to the depth of cut, surface roughness, and kerf taper. Arab et al [ 62 ] studied the effect of pump pressure and transverse feed rate on the cutting effect of abrasive water jets for cutting four types of rock and found that the removal volume and cutting rate of rocks increased with the increase in pump pressure and decrease in transverse feed rate, and the best cutting efficiency was obtained when the pump pressure was 400 MPa and the transverse feed rate was 200 mm/min. The best cutting efficiency was obtained at a pump pressure of 400 MPa and a transverse feed rate of 200 mm/min.…”
Section: Influencing Factors In the Processing Removal Process Of Abr...mentioning
confidence: 99%